Kesantunan Bertutur yang Terimplikasi dalam Penggunaan Verba Keigo - Astami, Timur Sri (Humaniora, 2012)
Keigo is variety honorific in Japanese language because there are aspects in which show patterns of respect shown to the listener. Keigo particular use can be seen on the verb form, consisting sonkeigo and kenjougo. The use of particular kinds of Keigo verbs consist of a principled kenjougo sonkeigo and civility. Keigo is important for Japanese learners, especially when they want to communicate attention to issues related between speaker and listener whom we said, what conditions, how the relationship with opponent , and more importantly, how to face protection of the partners. So that communication is established running properly and smoothly between speaker and listener.